2021
DOI: 10.1371/journal.pone.0250382
|View full text |Cite
|
Sign up to set email alerts
|

Potential for online crowdsourced biological recording data to complement surveillance for arthropod vectors

Abstract: Voluntary contributions by citizen scientists can gather large datasets covering wide geographical areas, and are increasingly utilized by researchers for multiple applications, including arthropod vector surveillance. Online platforms such as iNaturalist accumulate crowdsourced biological observations from around the world and these data could also be useful for monitoring vectors. The aim of this study was to explore the availability of observations of important vector taxa on the iNaturalist platform and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 103 publications
(140 reference statements)
0
18
0
Order By: Relevance
“…Even more rapid tick encounter information can be provided by online platforms with real time reporting. Such online platforms have shown great success in accomplishing this task in other countries [ 87 , 88 ] and, in Canada, eTick [ 89 ] is a dedicated online platform that allows the public to access tick recoveries in real-time.…”
Section: Discussionmentioning
confidence: 99%
“…Even more rapid tick encounter information can be provided by online platforms with real time reporting. Such online platforms have shown great success in accomplishing this task in other countries [ 87 , 88 ] and, in Canada, eTick [ 89 ] is a dedicated online platform that allows the public to access tick recoveries in real-time.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties associated with locating, observing, and collecting spider specimens partly account for the deficit of data on species ranges and diversity, and the lack of information on habitat and behavior (Cardoso, Erwin, Borges, & New, 2011). Community science initiatives (projects that partner researchers with community volunteers) help researchers expand arachnid research while also providing public outreach and education (Cull, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…An additional image-based approach that has shown potential to complement other tick surveillance strategies is the examination of tick images submitted to online wildlife databases such as iNaturalist [ 59 ]. The iNaturalist platform hosts a growing community of naturalists who submit primarily image-based wildlife observations via the iNaturalist smartphone app or website, where they can be identified by members of the community.…”
Section: Introductionmentioning
confidence: 99%
“…This valuable resource is being increasingly used in scientific research, and these studies demonstrate consistent results between community- and scientist-collected data [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. A previous analysis found that iNaturalist data concerning important tick and mosquito vectors correlated well with known geographical distributions and seasonality of these species [ 59 ].…”
Section: Introductionmentioning
confidence: 99%